The relationship between cervical length and area measurements evaluated by MRI and the amount of hemorrhage in PAS cases - Yue, Yongfei; Zhu, Liping; Liu, Chengfeng; Lu, Yanli (BMC pregnancy and childbirth, 2024)
Placenta accreta spectrum often leads to massive hemorrhage and even maternal shock and death. This study aims to identify whether cervical length and cervical area measured by magnetic resonance imaging correlate with massive hemorrhage in patients with placenta accreta spectrum. The study was conducted at our hospital, and 158 placenta previa patients with placenta accreta spectrum underwent preoperative magnetic resonance imaging examination were included. The cervical length and cervical area were measured and evaluated their ability to identify massive hemorrhage in patients with placenta accreta spectrum. The cervical length and area in patients with massive hemorrhage were both significantly smaller than those in patients without massive hemorrhage. The results of multivariate analysis show that cervical length and cervical area were significantly associated with massive hemorrhage. In all patients, a negative linear was found between cervical length and amount of blood loss (r =-0.613), and between cervical area and amount of blood loss (r =-0.629). Combined with cervical length and cervical area, the sensitivity, specificity, and the area under the curve for the predictive massive hemorrhage were 88.618%, 90.209%, and 0.890, respectively. The cervical length and area might be used to recognize massive hemorrhage in placenta previa patients with placenta accreta spectrum.